2010
DOI: 10.1002/adfm.201000074
|View full text |Cite
|
Sign up to set email alerts
|

Organically Functionalized Mesoporous Silica by Co‐structure‐Directing Route

Abstract: This article provides a brief overview of functional mesoporous silica materials synthesized by the co‐structure‐directing route, which is distinct from conventional synthesis strategies. In these systems, organosilane serves as the co‐structure‐directing agent (CSDA), which provides critical interactions between the template and organic part of the organosilane to form mesostructures, thus retaining the organic groups on the pore surface after removal of the template by extraction. i) The formation of anionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 120 publications
1
55
0
1
Order By: Relevance
“…From this, it can be concluded that only with a defined amount of sodium hydroxide, a well-pronounced pore system can be obtained and that therefore the amount of sodium hydroxide in the sol must be well adjusted. This strong dependence of the pore structure on the amount of sodium hydroxide or the alkalinity of the system has already been reported by Che et al [25]. The authors addressed the problem that under strong alkaline conditions CES is highly hydrated and therefore exhibit only weak interactions with the cationic headgroup of the surfactant.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…From this, it can be concluded that only with a defined amount of sodium hydroxide, a well-pronounced pore system can be obtained and that therefore the amount of sodium hydroxide in the sol must be well adjusted. This strong dependence of the pore structure on the amount of sodium hydroxide or the alkalinity of the system has already been reported by Che et al [25]. The authors addressed the problem that under strong alkaline conditions CES is highly hydrated and therefore exhibit only weak interactions with the cationic headgroup of the surfactant.…”
Section: Resultssupporting
confidence: 65%
“…Due to the negative charged carboxylate group of 5-(triethoxysilyl)-pentanoic acid, the organosilane serves as a co-structure-directing agent (CSDA), providing strong electrostatic interactions with the cationic headgroups of the CTAB micelles. This bridging effect of the CSDA between the organic and the inorganic species favors their self-organization and the formation of a periodically arranged pore systems [25,37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that the particle sizes can be tuned by controlling synthetic parameters, such as pH, reaction time and temperature [147][148][149][150][151][152][153][154][155][156][157][158][159], and by adding certain compounds such as organics and organosilanes [160][161][162]. These parameters are greatly associated with the hydrolysis and condensation of the silica sources (e.g., TEOS).…”
Section: Modified Stöber Methodsmentioning
confidence: 99%
“…Their large surface area and pore volume have found numerous applications in separation and adsorption techniques, they can play a role as a support for catalysis, costly biomolecules and drug delivery systems, moreover they found application in sensor industry, optoelectronics and recently in metamaterials study and fabrications [1][2][3][4][5][6][7][8][9][10][11][12]. Particularly silica as an inert and cost-effective material was in the focus of interest.…”
Section: Introductionmentioning
confidence: 99%